LDPC OVER MULTIHOP LORA NODES WITH PEELING DECODER - Rustanto
Wireless radio communication is expected to reach long distances with good quality. To achieve long-range radio communication, relay stations can be added between the source and destination points as needed. The wireless radio results in communication quality disturbances due to noise and interference. Therefore, detection and correction of errors in the received information are required. In this thesis, a multihop communication system was created using four stationary LoRa nodes. The Multihop LoRa system using a (32,16) reguler binary LDPC encoder for error correction and detection. Node-02 and node-03 as repeaters between node-01 and node-04. The LDPC decoder used is the Peeling technique. Each node is implemented using beaglebone black Industrial and LoRa ebyte. The software used includes debian console and python programming. Testing the multihop LoRa communication with LDPC peeling decoding will obtain information parameters such as multihop communication delay , error detection capability, and error correction capability, and RSSI LoRa.